Peran Pendidikan Karakter Berbasis Hadits di Wilayah Madrasah : The Role of Hadith Based Character Education in the Madrasa Area - Sandra Nestiya; Muhid (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2025)
In today's education world, character building based on hadith plays an important role in responding to the problem of declining moral and ethical values. The purpose of this study is to explore in depth the importance of implementing character education based on hadith in the madrasa environment. This study uses a literature study method with a descriptive-qualitative method, which aims to examine various relevant literature related to character education, hadith, and its implementation in the context of madrasas. The results of the study indicate that the hadith of the Prophet Muhammad SAW has great potential as a foundation in shaping students' character. Values ​​such as honesty, discipline, caring, and empathy contained in the hadith can be integrated into the curriculum and extracurricular activities of madrasas. The implementation of hadith-based character education in madrasas involves several strategies, including teacher role models. The implementation of hadith-based character education is greatly influenced by habituation in daily activities and through strong synergy between the madrasa and parents. This effort is expected to be able to form a generation that is not only noble, but also equipped with high spiritual and emotional intelligence, in accordance with the goals of comprehensive Islamic education.